2020
DOI: 10.3390/soilsystems4020032
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topographic Models for Mapping Soil Properties and Processes

Abstract: Landscape topography is an important driver of landscape distributions of soil properties and processes due to its impacts on gravity-driven overland and intrasoil lateral transport of water and nutrients. Rapid advancements in aerial, space, and geographic technologies have led to large scale availability of digital elevation models (DEMs), which have proven beneficial in a wide range of applications by providing detailed topographic information. In this report, we presented a summary of recent topography-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 118 publications
(168 reference statements)
0
11
0
Order By: Relevance
“…Similar conclusions were reported by Song et al [61], who noted that local environmental attributes play a less significant role than other predictors on a flat terrain system. Li et al [62] inferred that environmental attributes could capture large-scale influences of soil transport but not those occurring at a flat topographic condition. Thus, the over-employment of environmental factors in small-scale flat terrain areas reduces the prediction accuracy and increases the calculation complexity.…”
Section: Modeling Approach and Variables Of Importance In The Individ...mentioning
confidence: 99%
“…Similar conclusions were reported by Song et al [61], who noted that local environmental attributes play a less significant role than other predictors on a flat terrain system. Li et al [62] inferred that environmental attributes could capture large-scale influences of soil transport but not those occurring at a flat topographic condition. Thus, the over-employment of environmental factors in small-scale flat terrain areas reduces the prediction accuracy and increases the calculation complexity.…”
Section: Modeling Approach and Variables Of Importance In The Individ...mentioning
confidence: 99%
“…Many other studies confirmed the significant role of topography and its derivatives (elevation, slope and TWI) in the spatial distribution of SAS (Cantón et al, 2009;Tang et al, 2010;Nsabimana et al, 2020). Furthermore, we cannot forget the effect of the topography on other soil properties (Kumar and Singh, 2016;Li et al, 2020;Maleki et al, 2020;Tajik el al., 2020) and (Celik, 2005;Jin et al, 2008;Mahmoudabadi et al, 2017;Maynard and Levi, 2017), which will undoubtedly affect the distribution of soil stability. Besides all above results, we cannot forget the role of remote sensing parameters, which have shown their importance during this study.…”
Section: Determining the Relative Importance Of Variablesmentioning
confidence: 73%
“…Increasing As and tanβ causes the water flow rate and the amount of water to increase and, consequently, increases the erosive power of the water. It explains potential flow erosion and related land processes (Kalambukattu et al, 2018;Li et al, 2020) (1) et al, 2020) MSAVI minimizes the effect of bare soil on the Soil-Adjusted Vegetation Index (SAVI). MSAVI is calculated as a ratio between the R and NIR values with an inductive L function applied to maximize the reduction in soil effects on the vegetation signal Green Normalized Difference Vegetation Index (GNDVI) (Gitelson et al, 1996) Compared with the NDVI index, GNDVI is more sensitive to chlorophyll concentration.…”
Section: Index (Twi)mentioning
confidence: 99%